IMPLEMENTASI KURIKULUM TINGKAT SATUAN PENDIDIKAN DALAM LAYANAN PROFESI KONSELING - Mardiyani, Ani (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2009)
With the advent of Regulation No. 19/2005 on National Education Standards (NES), Permendiknas Number 24/2006,  Permendiknas Number. 22/2006 on the Implementation of Content Standards for Elementary and Secondary Education Unit, and Number. 23/2006 on Graduates Competency Standards for Basic Education Unit and medium, then we know LCEU (Level Curriculum Education Unit). In the curriculum structure of SD/MI, SMP/MTs, SMA/MA, and Vocational Schools Based VSB, there is a series of subjects at point A, point B on Local Content, and Self Development at point C. Subjects taught by subject teachers, class teachers or teachers 'practices'; local content as an extra-curricular activities; While self-development is not a subject that must be nurtured by teachers, but facilitated and/or guided by a counselor, teacher or educational staff that can be done in the form of extra-curricular activities. Self-development activities conducted through activities of counseling services on issues of social life and personal self, learning, and career development of students. As a teacher or counselor at school Advisors need to understand the implementation of LCEU in the profession of counseling services, so as to show the performance as a professional adviser. Which in turn will improve the quality of education in the global competition.